Edukasi dan Deteksi Dini Penyakit Diabetes Melitus - Tri Nugraha Susilawati; Sinu Andhi Jusup; Setyo Sri Rahardjo; Dono Indarto; Sri Wulandari; Yuliana Heri Suselo; Ratna Kusumawati; Heru Sulastomo; Niniek Purwaningtyas (Universitas Sebelas Maret, 2024)
Indonesia currently is experiencing a shift in disease patterns marked by a significant increase in the number of non-communicable diseases (NCDs), especially cardiovascular diseases, specifically diabetes mellitus (DM). A similar phenomenon also occurs in Surakarta city. Community service team conducts educational activities and health checks that aim to increase the knowledge of members of the Klub Jantung Sehat (KJS) related to cardiovascular disease as well as for screening risk factors for cardiovascular diseases including hypertension, hyperuricemia, diabetes mellitus (DM), and obesity. The methods used are counseling and checking blood pressure, uric acid, blood sugar at any time, and anthropometry. This community service activity was attended by 33 KJS members and was held on Sunday, 23 June 2024 at 07.00 - 09.00 at the Faculty of Sports, Sebelas Maret University (FKOR UNS) Jl. Menteri Supeno, Manahan, Banjarsari, Surakarta City, Central Java, however only 19 participants took part in the complete screening. The results achieved from this community service are an increase in the knowledge of KJS members related to cardiovascular diseases through discussions during counseling as well as during health checkups. The results of the health examination, it was found that 6 people (31.58%) had hypertension, 2 people (10.52%) had DM, and 11 people (57.89%) were found to meet the criteria of overweight and obesity. The members of KJS who had uric acid levels above normal were 10 people (52.63%). Similar activities should be carried out regularly and continuously as a preventive and promotive effort against non-communicable diseases in the community.